Role of Musculoskeletal Ultrasound and Matrix Metalloprteinase-2 serum Level in the Diagnosis of early Knee Osteoarthritis - Tarek Nasrallah; Hesham Abdel wahab; Mostafa Shakweer; Sabah Abd Al Raheem; Hanan Mehesin (International Journal of Medical Arts, 2020)
AbstractBackground: Osteoarthritis (OA) is the most common joint disease, causing disability and reduction of quality of life and participation in social activity. Now considered a whole joint disease, OA is characterized by cartilage loss, subchondral bone changes, synovial inflammation and meniscus degeneration1.Aim and objectives: The evaluation of the role of musculoskeletal ultrasound and MMP-2 serum in the diagnosis of early knee OA.Subjects and methods: The present study was conducted on 50 patients with early knee OA patients attending the Outpatients Clinic of the Rheumatology Department Damietta Faculty of Medicine, Al-Azhar University matched with 25 age and sex healthy volunteers. Musculoskeletal ultrasound (MUS) was performed by experienced radiologist according to the EULAR recommendations by using a 12–5-MHz linear transducer (voluson E6) and Metalloprteinase-2 (MMp2) was detected by Elisa technique.Results: MMP-2 is highly significant and overexpressed in patient group and its early detection is positively correlated with weight and BMI. Our results appear that family history, BMI and weight are the main risk factor for the onset of knee osteoarthritis (KOA) in the patient group. MUS clarifies most patients (88% and 80%) have Medium osteophyte on LT and RT respectively, followed by 44% of participants have Mild osteophyte on RT. Conclusion: MMP-2 is a diagnostic biomarker at the early stage of OA. MSU is an excellent imaging technique to detect early osteoarthritis.